2020
DOI: 10.1002/pol.20190156
|View full text |Cite
|
Sign up to set email alerts
|

Reversible swelling as a strategy in the development of smart membranes from electrospun polyvinyl alcohol nanofiber mats

Abstract: This work presents an electrospun nanofibrous membrane for water treatment, designed to reduce its pores through polymer swelling to retain contaminants, and after that, reopening them for easy cleaning. It consists of a polyvinyl alcohol (PVA) mat crosslinked with a natural agent to avoid water solubility but allow a high swelling of its nanofibers. Then, when the membrane is brought into contact with water, a transitory state occurs during which nanofibers increase their diameter 68%, closing the pores betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…An important characteristic of polymeric scaffolds for skin regeneration applications is their dehydration ability which is also referred as swelling reversibility. Swelling reversibility is interlaced to the reusability of the scaffolds [ 66 ]. Figure 8 c shows the relative water content of the samples and their behavior through the dehydration process.…”
Section: Resultsmentioning
confidence: 99%
“…An important characteristic of polymeric scaffolds for skin regeneration applications is their dehydration ability which is also referred as swelling reversibility. Swelling reversibility is interlaced to the reusability of the scaffolds [ 66 ]. Figure 8 c shows the relative water content of the samples and their behavior through the dehydration process.…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of reuse was confirmed for at least five cycles, and although the efficiency in the acid uptake decreased over the cycles, the lower achieved value is comparable to the one of commercial acid absorbent pads of sole use. 30 This decrease in the acid uptake efficiency over time until a steady state is reached (Figure 10), is the result of swelling reversal of a material's fibers as stated by Cimadoro et al 31 They found that a PVA membrane reversed its swelling 72% after the first cycle. 31 The possibility to completely regenerate the material through a desulfonation procedure was also explored.…”
Section: ■ Discussionmentioning
confidence: 86%
“…30 This decrease in the acid uptake efficiency over time until a steady state is reached (Figure 10), is the result of swelling reversal of a material's fibers as stated by Cimadoro et al 31 They found that a PVA membrane reversed its swelling 72% after the first cycle. 31 The possibility to completely regenerate the material through a desulfonation procedure was also explored. The sulfonic acid group (−SO 3 H) can be removed from a cyclic substrate by heating the sulfonated product in the presence of diluted aqueous sulfuric acid.…”
Section: ■ Discussionmentioning
confidence: 86%
See 2 more Smart Citations